Penerapan Model Pembelajaran Picture and Picture dalam Meningkatkan Hasil Belajar Siswa pada Muatan Bahasa Indonesia Kelas II SDN 116/X Lambur II - Sukaryanto Sukaryanto (Jurnal Ilmiah Dikdaya, 2022)
This study aims to reveal information and discuss the application of the Picture And Picture Learning Model in Improving Student Learning Outcomes in Indonesian Class II SDN 116 / X Lambur II. This research is included in the type of classroom action research (CAR). This research was conducted at SDN 116 / X Lambur II, Tanjung Jabung Timur Regency. This research was conducted in the even semester of the 2020/2021 academic year, starting in February 2021. The subjects in this study were class I students at SDN 116 / X Lambur II, Tanjung Jabung Timur Regency, totaling 30 people. The research procedure consisted of two cycles with each cycle having two meetings. Each cycle consists of four stages of research, namely planning, implementation, observation and reflection. Data collection in this study was carried out using field notes, student worksheets, written tests, and documents. Data analysis techniques used the percentage formula and data reduction. The results of this study indicate that using the Picture And Picture Learning Model in Indonesian Class II SDN 116 / X Lambur II can improve student learning outcomes by giving gifts.